Two new sesquiterpenoids produced by halophilic Nocardiopsis chromatogenes YIM 90109. Issue 1 (2nd January 2017) - Sun, Ming-Wei; Zhang, Xiao-Mei; Bi, Hui-Li; Li, Wen-Jun; Lu, Chun-Hua
Abstract: Two new germacradiene-type sesquiterpenoids, including 1(10) E, 5 E -germacradiene-9 β, 11-diol (or 9 β -hydroxyl germacradienol) (1 ) and 11-hydroxy-1(10) E, 5 E -germacradien-2-one (2-oxygermacradienol) (2 ), together with a known geosmin-type sesquiterpenoid (1 β, 4 β, 4a β, 7 α, 8a α )-4, 8a-dimethyloctahydronaphthalene-1, 4a, 7(2H)-triol (3 ), were elucidated by their NMR spectroscopic data, HR–ESI–MS and single-crystal X-ray diffraction from the halophilic strain Nocardiopsis chromatogenes YIM 90109. The antimicrobial activities were evaluated by paper diffusion method. Graphical Abstract: